Nano-power mixed-signal tunable edge-detection circuit for pixel-level processing in next generation vision systems - Constandinou,TG; Georgiou,J; Toumazou,C (Electronics Letters, 2003)
A useful nano-power circuit is presented for edge detection in integrated vision systems. Based on a compact front-end of only five MOS devices, this circuit features a tunable threshold and discrete output and is ideal for interfacing to digital electronics.